Early phase clinical studies of AR‐42, a histone deacetylase inhibitor, for neurofibromatosis type 2‐associated vestibular schwannomas and meningiomas. Issue 5 (20th August 2021) - Welling, D. Bradley; Collier, Katharine A.; Burns, Sarah S.; Oblinger, Janet L.; Shu, Edina; Miles‐Markley, Beth A.; Hofmeister, Craig C.; Makary, Mina S.; Slone, H. Wayne; Blakeley, Jaishri O.; Mansouri, S. Alireza; Neff, Brian A.; et al.
Abstract: Objectives: Two pilot studies of AR‐42, a pan‐histone deacetylase inhibitor, in human neurofibromatosis type 2 (NF2), vestibular schwannomas (VS), and meningiomas are presented. Primary endpoints included safety, and intra‐tumoral pharmacokinetics (PK) and pharmacodynamics (PD). Methods: Pilot 1 is a subset analysis of a phase 1 study of AR‐42 in solid tumors, which included NF2 or sporadic meningiomas. Tumor volumes and treatment‐related adverse events (TRAEs) are reported (NCT01129193). Pilot 2 is a phase 0 surgical study of AR‐42 assessing intra‐tumoral PK and PD. AR‐42 was administered for 3 weeks pre‐operatively. Plasma and tumor drug concentrations and p‐AKT expression were measured (NCT02282917). Results: Pilot 1: Five patients with NF2 and two with sporadic meningiomas experienced a similar incidence of TRAEs to the overall phase I trial. The six evaluable patients had 15 tumors (8 VS, 7 meningiomas). On AR‐42, tumor volume increased in six, remained stable in eight, and decreased in one tumor. The annual percent growth rate decreased in eight, remained stable in three, and increased in four tumors. Pilot 2: Four patients with sporadic VS and one patient with meningioma experienced no grade 3/4 toxicities. Expression of p‐AKT decreased in three of four VS. All tumors had higher AR‐42 concentrations than plasma. Conclusions: AR‐42 is safe. Tumor volumes showed a mixed response, but most slowed growth. On a 40‐mg regimen, drug concentrated in tumors and growth pathways were suppressed in most tumors, suggesting this may be a well‐tolerated and effective dose. A phase 2 study of AR‐42 for NF2‐associated tumors appears warranted. Level of Evidence: 1b, 4. Abstract :